The View from Nowhere - Brassier, Ray (Identities: Journal for Politics, Gender and Culture, 2011)
Author(s): Ray Brassier Title (English): The View from Nowhere Journal Reference: Identities: Journal for Politics, Gender and Culture, Vol. 8, No. 2 (Summer 2011) Publisher: Department of Gender Studies, Euro-Balkan Institute Page Range: 7-23 Page Count: 16 Citation (English): Ray Brassier, “The View from Nowhere,” Identities: Journal for Politics, Gender and Culture, Vol. 8, No. 2 (Summer 2011): 7-23.